2012
DOI: 10.1007/s00405-011-1919-x
|View full text |Cite
|
Sign up to set email alerts
|

Long-term efficacy of submucosal uvulopalatopharyngoplasty for obstructive sleep apnea syndrome

Abstract: The objective of the study was the assessment of the long-term efficacy of submucosal uvulopalatopharyngoplasty in patients with obstructive sleep apnea syndrome. Thirty-two of 156 patients who underwent UPPP between January 2001 and March 2007 with a follow-up period of 36-96 months (mean, 56 months) were included in the study conducted at the university affiliated center. Preoperative and postoperative snoring evaluation forms and Epworth Sleepiness Scale (ESC) scores were used for subjective analysis. Preop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…Therefore, the results of the overall surgical response or cure rate in these studies should be lower by the common criteria. In fact, for the 6 studies 20,21,24,26-28 meeting the criteria of AHI, RDI, or ODI decreasing ≥50% and to ≤20 events/h, the pooled long-term SRR was 46.5% (95% CI, 40.3%-52.8%; n = 117 of 252), while the pooled long-term SRR of the 3 studies 21,26,27 with the criteria of AHI decreasing ≥50% and to ≤20 events/h was 48.3% (95% CI, 39.3%-57.4%; n = 59 of 122). The 3 studies with the criteria of long-term AHI <5 for surgical cure resulted in a pooled long-term SCR of 32.3% (95% CI, 23.9%-41.7%; n = 36 of 112).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the results of the overall surgical response or cure rate in these studies should be lower by the common criteria. In fact, for the 6 studies 20,21,24,26-28 meeting the criteria of AHI, RDI, or ODI decreasing ≥50% and to ≤20 events/h, the pooled long-term SRR was 46.5% (95% CI, 40.3%-52.8%; n = 117 of 252), while the pooled long-term SRR of the 3 studies 21,26,27 with the criteria of AHI decreasing ≥50% and to ≤20 events/h was 48.3% (95% CI, 39.3%-57.4%; n = 59 of 122). The 3 studies with the criteria of long-term AHI <5 for surgical cure resulted in a pooled long-term SCR of 32.3% (95% CI, 23.9%-41.7%; n = 36 of 112).…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies 18,20,21,23-28 provided data of long-term SRR from 28.6% to 55% with inconsistent criteria ( Table 5 ). The pooled analysis of the 9 studies resulted in an SRR of 44.4% (95% CI, 39.1%-49.7%; n = 155 of 350) without heterogeneity or inconsistency ( Q statistic P = .42; I 2 = 1%; Figure 3 ).…”
Section: Srr and Scrmentioning
confidence: 99%
See 1 more Smart Citation
“…The criteria of success vary according to the study. [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29] Therefore, the treatment outcome cannot be directly compared on a common platform between studies. Our study also showed that the success rate ranged from 44.9% to 70.4%, according to the criterion applied.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment success was defined by the following 6 criteria used in the literature: (1) posttreatment AHI < 10/h 11,14,17 ; (2) posttreatment AHI < 20/h 15,20 ; (3) reduction in the AHI > 50% and posttreatment AHI < 10/h 27 ; (4) reduction in the AHI > 50% and posttreatment AHI < 15/h 12,28 ; (5) reduction in the AHI > 50% and posttreatment AHI < 20/h 10,13,18,21,23,25,26 ; and (6) a reduction in the AHI > 50%. 24,29 …”
Section: Criteria Of Treatment Successmentioning
confidence: 99%